Islamic Religious Education As A Form - Nadia Nadia; Arrohman Arrohman (Proceeding International Seminar of Islamic Studies, 2019)
Islamic education is a whole human education, Mind and Heart, His spiritual and temporal, and her skills. Here Islamic education is a process of individual formation based on the teachings of Islam revealed by Allah SWT, More emphasis on Islamic education meaning "guidance", Emphasis on the meaning of Islamic education more to "not" teaching "containing the authorist connotations of educational executor, The human of Kamil originated in Arabic, Namely of the two words: Insan and Kamil. Arab, Literally, Insan means man, and Kamil means perfect. Thus, the people of Kamil mean the perfect man. The word human has three word origins. First, it comes from the word that has the meaning of seeing, knowing and asking for permission. The second one, derived from the word fate that means forgetting. The third is derived from the al-uns meaning tame, the opposite of the savage word. By resting on the origin of the word Anasa, the human beings contain the meaning of seeing, knowing and asking for permission and all these meanings are related to human ability in the field of reasoning, so as to receive instruction. With guidance in accordance with Islamic teachings, then the students have ample space to actualize all the potential that it possesses.